Pengembangan Modul Multirepresentasi Berbasis Android Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa - Dimas Permadi (Program Studi Pendidikan Fisika, UIN Raden Fatah Palembang, 2021)
This study aims to describe the development and to produce an android-based multi-representation module that can improve students' critical thinking skills that are suitable for use as a learning medium. The method used is a 4-D model development research with development steps, namely define, design, development, and disseminate. In this research, development is only carried out until the development stage. Based on the results of the development, it was obtained the validation results of material and design experts with ideal assessment scores of 70 and 73 and peers 1 and 2 respectively 66 and 75, the cut off value obtained was 70.5 so that the developed module was declared fit for use in a construct. The improvement of students' critical thinking skills after using the android-based multi-percentage module had moderate criteria with a gain of 0.468 and 77% of students achieved the Minimum Completeness Criteria (KKM).